TYPES AND SEMANTIC CATEGORIES OF TAI PHUAN CLASSIFIERS: A STUDY IN COGNITIVE SEMANTICS - Aree, Usana; Wongwattana, Unchalee (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This research examined the types and semantic categories of classifiers in Tai Phuan language from a cognitive semantic perspective. This research was a qualitative study using a descriptive method. The research tools included a wordlist and a set of guiding questions used for collecting field data. The study identified a total of 275 classifiers in Tai Phuan language and analyzed them across three dimensions: classifier types, semantic categories, and prototype characteristics. Types of Tai Phuan classifiers can be divided into two main categories: (1) Classifiers for nouns, which were further categorized into five subtypes: kind-based meaning, perceptual meaning, collective meaning, measurement units, and action-based meaning, and (2) Classifiers for verbs, which were divided into two subtypes: classifiers used with bounded actions and classifiers used with unbounded actions. Semantic categories of Tai Phuan classifiers were organized according to their fundamental meanings that appeared in everyday contexts before extending to various contextual applications. Eight semantic categories were identified: object, shape/form, human, location, plant, abstract concepts, animal, and vehicle. This categorization reflected how basic semantic properties in daily life served as the foundation for broader contextual meaning extensions. The prototype of Tai Phuan classifiers based on the concept that prototypical classifiers must possess genuine classifier properties, namely frequent occurrence and compatibility with a diverse range of modified words. The findings revealed that the most prototypical classifier for nouns was /ɂan2/ while the most prototypical classifier for verbs was /thɨ:4/. Both classifiers demonstrated remarkable versatility, functioning as classifiers for lexical items across numerous categories and a wide variety of words.